Transcriptomic Analysis of Macrophages Infected with Mycobacterium smegmatis - Hong Sun; Yue Hou; Wenzhao Xu; Wenjing Wang; Na Tian; Dingyi Liu; Zhaogang Sun (Microbiology Research, 2025)
Mycobacterium tuberculosis (MTB) can cause serious infectious diseases. MTB is retained in the macrophages of an organism, activating the immune response or evading the immune response through other mechanisms. Mycobacterium smegmatis (M. smeg) has the advantage of high safety and maneuverability as an alternative to MTB. M. smeg has physiological functions similar to those of MTB. It is mainly used to study the molecular mechanism of the interaction between the modified M. smeg carrying MTB-related components and cells. There are few studies on the interaction between the unmodified M. smeg and macrophages. Transcriptomics is an emerging research tool in recent years, which can deeply explore the relevant molecules inside a cell and explore the possible regulatory mechanisms more comprehensively. In this study, we first constructed an in vitro model of M. smeg-infected macrophages, collected RNA extracted from the infected cells, performed transcriptome sequencing using the Illunima platform, and verified the expression levels of the main markers related to phenotypic or functional changes in macrophages by qPCR and ELISA. In this study, through the transcriptomic analysis of M. smeg-infected macrophages, we found that M. smeg can regulate multiple cell signaling pathways in macrophages dominated by immune responses and activate the production of the cytokines IL-6 and TNF-α, which are mainly involved in the immune response in macrophages. This study suggests that M. smeg and MTB have similar physiological functions in activating the immune response of macrophages. Meanwhile, the interaction between M. smeg and macrophages also indicates the primary position and significant role of immune regulation in cellular signaling pathways. Therefore, studying the interaction mechanism between macrophages and M. smeg through transcriptomics is conducive to a comprehensive understanding of the related physiological functions of M. smeg in regulating immune responses or immune escape, providing strong evidence for its use as a model alternative bacteria for MTB in the future research on MTB immunity and related physiological functions.